The Centenary Of The Torrens System In Malaysia - Teo, Keang Sood (Journal of Malaysian and Comparative Law, 2019)
The Centenary Of The Torrens System In Malaysia edited by Tan Sri Datuk Professor Ahmad Ibrahim and Judith Sihombing is indeed a valuable edition to the legal literature currently available on the Malaysian Torrens system. It is a valuable source of referece to those who seek to undertake research on certain aspects of the Malaysian Torrens system.